Efektivitas Penggunaan Alat Peraga “PAPI GO!” Pada Mata Pelajaran Matematika SMK Pokok Bahasan Trigonometri - Devika Amelia Nurjanah; Tina Sulistianingsih; Syafira Rizqi Pratiwi; Fradinda Amelia Hapipah; Casilta Widianti; Muhammad Giri Tarmizi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Mathematics is a branch of science that is very useful in social life. Trigonometry is a branch of mathematics that studies relationships including lengths and angles in triangles. Trigonometry is a branch of mathematics that will only be taught to high school/vocational school level students, so for students trigonometry is a new and abstract subject so it is difficult to understand. This research aims to enable students to overcome difficulties and obstacles to student learning in learning trigonometry using this teaching aid. This research method uses the library research method. The use of teaching aids in mathematics learning is very important and much needed for vocational high school students. PAPI GO! learning media can be a support or support in mathematics learning which can increase students' learning motivation in trigonometry material.